Relationship between shift work and the risk of colorectal cancer among Moroccan women - Elbaylek, Hamza; Ammor, Soumia (Intelektual Pustaka Media Utama, 2025)
Colorectal cancer (CRC) is a public health problem worldwide, and also in Morocco, with 7.9% of new cancer cases. Dietary factors have been linked to CRC risk; however, several modifiable risk factors have not been studied in Morocco. This study aimed to explore the association between shift work and the risk of colorectal cancer among Moroccan women. A case-control study was conducted at CHU Mohamed VI Marrakech, involving 165 cases and 165 controls. Data were collected using a self-administered questionnaire. For general characteristics, we used the Chi-square test for categorical variables and student’s t-test or Mann-Whitney U for continuous variables to select confounding factors, we ran logistic regression analysis to estimate odds ratios and 95% confidence intervals. Findings from our study show an increased risk of CRC for rotating shift workers ORb:1.74 (95% CI:1.05-2.91) (p-value = 0.01). When stratified by tumor location, night shift work was correlated with an increased risk of rectal cancer, while stratified by age, rotating shift work was also correlated with an increased risk of CRC among those aged 45 to 65 years ORb: 2.18 (95% CI:1.03-4.79) (p-value = 0.048). Findings from this study may be helpful for future research in Morocco and North African countries.